Effect of Nigella Sativa Extract on Inflammatory Cells, Interleukin-10, Interferon-Î³ and Histological of Kidney in Monosodium Glutamate-Induced Rats - Abdalrauf A Mahmud Yousif; Hidayat Sujuti; Edi Widjajanto (Journal of Tropical Life Science, 2016)
There is considerable evidence, suggest that, consumption of food additives monosodium glutamate (MSG), a flavor enhancer was unhealthy. Herbal medicine Nigella sativa (NS) has antioxidant properties able to cure the toxic induced by MSG. This study aimed to evaluate the risks of excessive use of MSG and to study the role of NS to inhibit inflammation and renal damage. Treated rats (twenty four male wistar rats) were divided into six group and analyzed by measuring the cells in blood, interleukin-10, interferon-Î³ serum levels by ELISA method and remove kidneys for histological examination. Histological of kidney for all groups except control, were showed different abnormalities include congestion of some blood vessels, hemorrhageÂ  between tubules, widening in the renal tubules, revealed severe dilatation of Bowman's capsule and shrinkage of glomeruli, and areas of huge vacuole, were observed compared with control. Interleukin-10 was reduced in Groups 2,3,4 and 5, whereas increase in NS group compared with control. Interferon-Î³ was increased in groups 2,3,4 and reduced in groups 5,6 compared with control.Â  Eosinophil was increased in groups 2,5 and reduced in groups 3,4, 6 compared with control. This present study showed that administration of MSG to rats induced many changes effects on inflammatory cells, cytokines and histological of kidneys. NS has benefit in blood parameters, whereas harmful on kidney at these doses.